2006
DOI: 10.1086/498742
|View full text |Cite
|
Sign up to set email alerts
|

Deep Near‐Infrared Observations of L1014: Revealing the Nature of the Core and Its Embedded Source

Abstract: Recently, the Spitzer Space Telescope discovered L1014-IRS, a mid-infrared source with protostellar colors, toward the heretofore ''starless'' core L1014. We present deep near-infrared observations that show a scattered light nebula extending from L1014-IRS. This nebula resembles those typically associated with protostars and young stellar objects, tracing envelope cavities presumably evacuated by an outflow. The northern lobe of the nebula has an opening angle of $100, while the southern lobe is barely detect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 43 publications
5
58
2
Order By: Relevance
“…Crapsi et al (2004) explain this by suggesting that L1521F is less chemically evolved and has a molecular hole of radius < 2000 AU. Onishi, Mizuno & Fukui (1999) have speculated that the spatially compact (<30 ) line wings seen in HCO + (3-2) lines may be due to bipolar outflow emission similar to that seen from L1014-IRS by Huard et al, (2006). A well-defined bipolar scattered light nebula seen at short wavelengths (<5 µm) by Bourke et al, (2006) also suggests the presence of molecular outflows in L1521F similar to those from low-mass protostars.…”
Section: L1521fmentioning
confidence: 93%
“…Crapsi et al (2004) explain this by suggesting that L1521F is less chemically evolved and has a molecular hole of radius < 2000 AU. Onishi, Mizuno & Fukui (1999) have speculated that the spatially compact (<30 ) line wings seen in HCO + (3-2) lines may be due to bipolar outflow emission similar to that seen from L1014-IRS by Huard et al, (2006). A well-defined bipolar scattered light nebula seen at short wavelengths (<5 µm) by Bourke et al, (2006) also suggests the presence of molecular outflows in L1521F similar to those from low-mass protostars.…”
Section: L1521fmentioning
confidence: 93%
“…However, Spitzer observations of L1014, which is considered as a starless core, as a part of Spitzer Legacy program "From Molecular Cores to Planet Forming Disks" (or c2d; Evans et al 2003) came as a surprise! The core L1014 was found to contain an embedded source, L1014−IRS, with a very low luminosity of L ∼ 0.09 L (Young et al 2004;Bourke et al 2005;Huard et al 2006). The VeLLOs in fourteen more cores were identified in the full c2d sample (Dunham et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…0.1 L , (Young et al 2004;Bourke et al 2005;Huard et al 2006). Interestingly, L1014 shows very little evidence of being an evolved core (Crapsi et al 2005b).…”
Section: Introductionmentioning
confidence: 99%